ANALISIS KINERJA KEUANGAN PEMERINTAH KOTA BENGKULU MENGGUNAKAN METODE VALUE FOR MONEY - Manullang, Stevania; Fadli, Fadli (COMPETITIVE, 2024)
The role of the Bengkulu City government in public services is crucial to assess the region's financial strength and the success of financial autonomy. The Bengkulu City Financial and Asset Management Agency (BPKAD) should focus on value for money in its activities. This study aims to evaluate the financial performance of  BPKAD Bengkulu City from 2018 to 2022 using a value for money approach, considering economy, efficiency, and effectiveness. This research is a quantitative descriptive study conducted at BPKAD Bengkulu City, using literature review and documentation for data collection, and analyzed using Economic Ratio, Efficiency Ratio, and Effectiveness Ratio. The results show: in the 2018 fiscal year is include the criteria of economic, less efficient, and very effective. In the 2019 fiscal year, the criteria for assessing financial performance are economical, less efficient, and effective. The 2020 fiscal year with the criteria of being quite economical, inefficient, and less effective.  In the 2021 fiscal year, it is included in the criteria of being quite economical, less efficient, and quite effective. Then for the 2022 fiscal year, the assessment of financial performance is included in the criteria of economy, less efficiency, and effectiveness.